(untitled) (Journal of Atomic and Molecular Sciences, 2012)
We apply BBK, DS3C model and the new modified Sommerfeld parameters of the present DS3C model to calculation of the triple differential cross sections (TDCS) for electron impact ionization of helium in the perpendicular plane symmetric geometry. The results of the present are compared with the measurements and those of other theoretical models. It was found that the present results give a better description for the experimental data and the dynamical screening effects are strong in this geometry. The influence of the Sommerfeld parameters on the triple differential cross sections is also analyzed and discussed in the perpendicular plane geometry.